The vital components of hipster cafe that affect millennials’ satisfaction / Intan Rafidah Ismail and Nur Iman Aqilah Shahril - Ismail, Intan Rafidah; Shahril, Nur Iman Aqilah (Faculty of Business Management, 2016)
Hipster café has been receiving a significant attention from all over the world. Malaysia is also one of the countries that has been boomed with many opening of hipster café which leave the population astounded. Millennials especially has been paying a lot of attention to this hipster café phenomenon. This research is conducted to see what makes the millennials satisfied from their visit to the hipster café because there are no discoveries regarding this matter in the previous year under the Malaysia context yet. A few variables of restaurant quality dimension is tested to see the relationship between millennials’ satisfaction and hipster café. Those variables would be food quality, restaurant quality, physical environment and price fairness. The researchers chose to conduct the research specifically on students of UiTM (Malacca) City Campus with the total population 2,250. 331 questionnaires were distributed to hipster café goers in UiTM (Malacaa) City Campus and the data were analyzed. Supporting data from other previous researcher in accordance to millennials and restaurants quality dimension were also acquired to assist in adding more strength to the findings. The research is concluded with the recordings of the data, analysis, result and recommendations made by the researchers